State of the art review of wind induced vibration and its control on transmission towers. (February 2021) - Roy, Swabarna; Kundu, Chinmay Kumar
Abstract: Transmission towers are used widely for transmitting electric power as there is a huge requirement of electricity consumption in every developing country. Structural design of steel transmission towers under the wind loading condition plays a crucial role in power sector and in human life. Wind loads are randomly applied dynamic loads acting more at higher altitudes from ground level. Various research done on steel tower response to wind loading have shown that wind causes stress among the large number of structural components which makes the analysis of tower less accurate. This further creates structural damage to the tower and leads to failure. In this paper, a brief review on the analysis and structural modelling under wind loading has been presented. Various literatures have shown that wind induces a huge amount of vibration to the structure during its service life. Control strategies used by researchers make use of damping devices such as VED, TMD, MR and Friction damper which controls the wind induced vibration on towers. A comparative study is done based on the performance of various dampers in reducing the structural vibration responses. Friction damper is found to be more efficient and robust in reducing the wind induced vibration on towers.